Utility of the TG/HDL-C Ratio in Estimating Pediatric Cardiometabolic Risk in a Community Hospital - Adeola O. Awujoola; Ana P. Torga; Jose E. Valencia; Hermella Alemneh; Olaseni P. Prince; Sandipagu P. Kant (Children)
Background: The evaluation of metabolic syndrome (MetS) is critical among children and adolescents as it can predict cardiovascular disease in adulthood. The TG/HDL-C ratio has the best predictive accuracy among the different lipid ratios. This study aims to evaluate the prevalence and factors associated with a high TG/HDL-C ratio and the predictive accuracy for pediatric MetS. Methods: This is a cross-sectional study of adolescents aged 9–21 to determine the prevalence of and associations between an elevated TG/HDL-C ratio and MetS. A ROC curve analysis was performed to determine the predictive accuracy of TG/HDL-C with MetS. Results: Of the 604 subjects, 29.8% had elevated TG/HDL-C, MetS was identified in 28.2%, and 54.5% were obese. Among patients with MetS, those with obesity were more likely to have an elevated TG/HDL-C ratio compared to those with a normal BMI (64% vs. 14%, p < 0.05). Gender, obesity, ethnicity, and METS are significantly associated with a high TG/HDL-C ratio. TG/HDL-C has a good discriminatory ability to distinguish patients with MetS from those without (AUC 0.65, p < 0.05). Conclusions: The TG/HDL-C ratio was able to distinguish between children and adolescents with MetS. Hence, the TG/HDL-C ratio may be used in the rapid risk assessment of pediatric MetS, especially in those with obesity.